2015
DOI: 10.1371/journal.pone.0128128
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Angiostrongylus cantonensis/mackerrasae Complex in Molluscs from the Sydney Region

Abstract: Angiostrongylus cantonensis and Angiostrongylus mackerrasae are metastrongyloid nematodes that infect various rat species. Terrestrial and aquatic molluscs are intermediate hosts of these worms while humans and dogs are accidental hosts. Angiostrongylus cantonensis is the major cause of angiostrongyliasis, a disease characterised by eosinophilic meningitis. Although both A. cantonensis and A. mackerrasae are found in Australia, A. cantonensis appears to account for most infections in humans and animals. Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Angiostrongylus cantonensis was initially discovered in China [ 4 ], and in Hawai‘i the first human case of angiostrongyliasis was reported in 1959 [ 5 ]. This zoonotic pathogen is also found in Asia, Australia, Brazil, the Caribbean islands and other Pacific Islands and has spread to and within the US continent (Louisiana, Texas, Oklahoma, and Florida) with more than 2,800 cases of human infection reported in 30 countries [ 2 , 6 , 7 , 8 ]. Angiostrongylus cantonensis is typically described as a tropical parasite but it appears to be adapting to gastropod hosts found in more temperate climates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Angiostrongylus cantonensis was initially discovered in China [ 4 ], and in Hawai‘i the first human case of angiostrongyliasis was reported in 1959 [ 5 ]. This zoonotic pathogen is also found in Asia, Australia, Brazil, the Caribbean islands and other Pacific Islands and has spread to and within the US continent (Louisiana, Texas, Oklahoma, and Florida) with more than 2,800 cases of human infection reported in 30 countries [ 2 , 6 , 7 , 8 ]. Angiostrongylus cantonensis is typically described as a tropical parasite but it appears to be adapting to gastropod hosts found in more temperate climates [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, molecular studies were lacking for A. mackerrasae compared to the other members ( A. cantonensis and A. malaysiensis ) of the A. cantonensis species complex. A recent study indicates that A. mackerrasae and A. cantonensis are almost identical at two genetic loci (the nuclear internal transcribed spacer (ITS)-1 and 18S rRNA genes), indicating that these two taxa are conspecific (Chan et al , 2015). Another study, based on restriction enzymes for the cox3 region, failed to distinguish A. mackerrasae from A. cantonensis (Aghazadeh, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…As for A. malaysiensis , A. mackerrasae , when first documented in Australia, was referred to as A. cantonensis (Mackerras & Sandars, 1954, 1955). Recent studies based on molecular markers indicate that it is highly similar to A. cantonensis (Aghazadeh, 2015; Aghazadeh et al , 2015; Chan et al , 2015). These studies did not include A. malaysiensis , another member of the A. cantonensis species complex, for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, neither Chan et al . (2015) nor Song et al . (2018) synonymized the two species, indicating that more information is needed to resolve their status as distinct species, subspecies or synonyms.…”
Section: Explanatory Informationmentioning
confidence: 88%
“…However, Chan et al . (2015) detected little or no difference in 18S and ITS1 sequences between the two species, and Song et al . (2018) showed that the two species were extremely similar on the basis of mitochondrial DNA sequences.…”
Section: Explanatory Informationmentioning
confidence: 91%